Pengembangan Video Pembelajaran Terintegrasi Profil Pelajar Pancasila pada Materi Kimia Hijau: Penelitian - Risma Della Elviani Rovita; Asrial; Fatria Dewi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Research has been carried out on the development of integrated learning videos of Pancasila Student Profiles on green chemistry materials. The purpose of this research is to determine the feasibility of developing integrated learning videos on the Pancasila Student Profile according to the validation of subject matter experts and media experts, to understand teachers' assessments, and to gauge students' responses to the developed media. This research uses the Lee & Owens development model, which consists of the stages of analysis, design, development, implementation, and evaluation. The developed product is validated by subject matter experts and media experts, and then evaluated by chemistry subject teachers, after which it is tested on a small group. The data analysis techniques used were qualitative and quantitative data analysis. The results of this study indicate that the integrated learning video on the Pancasila Student Profile received a material expert validation score of 4.3 in the Very Feasible category, a media expert score of 4.8 in the Very Feasible category, a teacher assessment score of 4.54 in the Very Feasible category, and received very good responses from students with a student response percentage of 89.69%. Based on the results obtained, it can be concluded that the integrated Pancasila Student Profile learning video on green chemistry material that has been developed is suitable for use as one of the media in the chemistry learning process.